Effect of some affective and demographic variables on life satisfaction of infertile women - D Seif; Sh Alborzi; S Alborzi (JRI, 2001)
Various studies show that infertility is related to affective problems such as depression, despair, psychological stress, anxiety and also dissatisfaction from marital life. The purpose of this research was investigation of effect of some affective and demographic variables on life satisfaction of infertile women. Affective factors were such as having husband’s support, others blame, report of feeling psychological stress, anxiety, despair, depression and isolation and demographic factors were age, educational background, social status of couple and the kind of family. Sample group was composed of 77 women (mean age 26) who had referred for infertility treatment to one of treatment centers in Shiraz. Individual information questionnaire, which was prepared by researchers ad its integrity was being checked by specialists, was used to gather demographic information and other affective factors. For evaluation of life satisfaction “Temporal Satisfaction With Life Scale” (TSWLS) was used. This scale evaluates the satisfaction of people in 3 stages of past, present and future life. Its integrity has been evaluated in this study. Regression analysis of multiple variable was used for information and despair caused past, present and future lie dissatisfaction of infertile women but husband’s support and also his social status increase the life satisfaction of these women and also all other stages of life. Living in nuclear family results in increase of present and future life satisfaction of infertile women. As for total conclusion, data shows that effect of affection and demographic variables on the life satisfaction of infertile women is not equal.
Keywords: Infertility, Affective factors, Demographic factors, Life satisfaction